2008
DOI: 10.1124/mol.108.050609
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Activation of Peroxisome Proliferator-Activated Receptor-β/δ Inhibits Cell Proliferation in Human HaCaT Keratinocytes

Abstract: Although

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
72
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(83 citation statements)
references
References 47 publications
8
72
3
Order By: Relevance
“…3 and 4). These results are consistent with findings by others showing that ligand activation of PPAR␤/␦ by GW0742 and GW501516 increases expression of PPAR␤/␦ target genes, but atRA and 9cRA do not (Borland et al, 2008). The same authors also showed that both the synthetic PPAR␤/␦ ligand GW0742 and atRA inhibit HaCAT cell proliferation, but only inhibition of cell growth by GW0742 is dependent on the presence of PPAR␤/␦.…”
Section: Discussionsupporting
confidence: 82%
“…3 and 4). These results are consistent with findings by others showing that ligand activation of PPAR␤/␦ by GW0742 and GW501516 increases expression of PPAR␤/␦ target genes, but atRA and 9cRA do not (Borland et al, 2008). The same authors also showed that both the synthetic PPAR␤/␦ ligand GW0742 and atRA inhibit HaCAT cell proliferation, but only inhibition of cell growth by GW0742 is dependent on the presence of PPAR␤/␦.…”
Section: Discussionsupporting
confidence: 82%
“…C and D, fetal lung fibroblasts established from a mouse strain with a floxed Pparb/d allele (Barak et al, 2002) were infected with either the empty retroviral vector (pBabe; left) or a Cre-expressing retrovirus (pBabeCre; right) (Li et al, 1997) mains unclear. The description of PGI 2 (prostacyclin) (Gupta et al, 2000;Hatae et al, 2001) and all-trans retinoic acid (Schug et al, 2007) as PPAR␤/␦ agonists are in conflict with data published by us (Fauti et al, 2006;Rieck et al, 2008) and by others (Yu et al, 1995;Forman et al, 1996;Borland et al, 2008). Unsaturated fatty acids have been reported to interact with the PPAR␤/␦ LBD (Forman et al, 1996;Xu et al, 1999), but their effect on the transcriptional activity of PPAR␤/␦ is weak .…”
Section: Discussioncontrasting
confidence: 49%
“…In this context, it is also noteworthy that the agonistic effect of 15-HETE on PPAR␤/␦ was particular high is keratinocytes (HaCaT cells; Fig. 5B), where a growth-inhibitory role for PPAR␤/␦ is well established (Michalik et al, 2001;Kim et al, 2006;Burdick et al, 2007;Borland et al, 2008;Girroir et al, 2008;Chong et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…In a genetically modified animal model, intestinal tumorigenesis, but not colon carcinogenesis, was increased in response to GW501516 (Gupta et al, 2004). On the other hand, mice lacking PPAR␦ have an increased predisposition to intestinal tumors (Reed et al, 2004); other reports suggest that ligand activation of PPAR␦ is without effect (Hollingshead et al, 2007) or, in fact, inhibits growth of human cancer cell lines (Bility et al, 2008;Borland et al, 2008) and colon carcinogenesis in mice (Marin et al, 2006). PPAR␦ is a key regulator of skeletal muscle lipid oxidation, and, as outlined in section III, activation of PPAR␦ should have many potential beneficial effects in the context of metabolic disease.…”
Section: A What Will Be the Therapeutic Impact Of Peroxisome Prolifementioning
confidence: 96%